2012
DOI: 10.1021/la300978x
|View full text |Cite
|
Sign up to set email alerts
|

UV-Modulated Substrate Rigidity for Multiscale Study of Mechanoresponsive Cellular Behaviors

Abstract: Mechanical properties of the extracellular matrix (ECM) have profound effects on cellular functions. Here, we applied novel photosensitive poly-dimethylsiloxane (photoPDMS) chemistry to create photosensitive, biocompatible photoPDMS as a rigidity-tunable material for study of mechanoresponsive cellular behaviors. By modulating the PDMS crosslinker to monomer ratio, UV light exposure time, and post-exposure baking time, we achieved a broad range of bulk Young’s modulus for photoPDMS from 0.027 - 2.48 MPa. Bioco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…[117] Thus, it is likely that adherent cells, during cell spreading and migration, will exert forces to the micropost tops through adhesion areas much smaller than the micropost top surface, and thus the cells will be able to sense the local intrinsic nanoscale material stiffness (i.e., bulk Young ’s modulus) of the PDMS micropost (Figure 4e). [112,118] Our finite element simulation (FEM) results in Figure 4e indeed demonstrated that the adhesion area through which a contractile force was applied had a non-negligible effect on the overall effective spring constant of the PDMS micropost, even when the bulk Young ’s modulus of PDMS remained as 2.5 MPa. It is expected that when softer elastomeric materials are used to fabricate micropost structures [112] , the effects of local force application and FA size can become much more significant and maybe even dominate the effect of the overall structural stiffness of the micropost.…”
Section: Toolbox Of Micro/nanoengineered Functional Biomaterialsmentioning
confidence: 76%
“…[117] Thus, it is likely that adherent cells, during cell spreading and migration, will exert forces to the micropost tops through adhesion areas much smaller than the micropost top surface, and thus the cells will be able to sense the local intrinsic nanoscale material stiffness (i.e., bulk Young ’s modulus) of the PDMS micropost (Figure 4e). [112,118] Our finite element simulation (FEM) results in Figure 4e indeed demonstrated that the adhesion area through which a contractile force was applied had a non-negligible effect on the overall effective spring constant of the PDMS micropost, even when the bulk Young ’s modulus of PDMS remained as 2.5 MPa. It is expected that when softer elastomeric materials are used to fabricate micropost structures [112] , the effects of local force application and FA size can become much more significant and maybe even dominate the effect of the overall structural stiffness of the micropost.…”
Section: Toolbox Of Micro/nanoengineered Functional Biomaterialsmentioning
confidence: 76%
“…Compared with fibrous mesh structures made from collagen, fibrin, or polymer fibers, the 3D patterned substrates generated with our method are mechanically stiffer, but have the advantage of providing well-defined geometric presentation of ECM at cellular length scales. However, it is expected that the stiffness could be reduced to a more appropriate physiological level by using this fracture-based technique with alternative substrate materials such as Sylgard 527 gel 55 or UV-modified PDMS 26 .…”
Section: Resultsmentioning
confidence: 99%
“…This makes it problematic for cell culture studies where the PDMS will be placed in a 37°C incubator for prolonged periods of time and the elastic modulus will increase. With the goal of spatially patterning the mechanical properties, Sun et al have developed an approach that uses benzophenone added to the Sylgard 184 as a photo initiator to reduce the crosslink density when exposed to UV light [69]. This can produce Sylgard 184 with an elastic modulus as low as 27 kPa when formulated with a base to curing agent ration of 30∶1 and short curing times of 20 minutes at 110°C.…”
Section: Discussionmentioning
confidence: 99%